2018
DOI: 10.1111/ene.13823
|View full text |Cite
|
Sign up to set email alerts
|

High burden of neurological disease in the older general population: results from the Canadian Longitudinal Study on Aging

Abstract: Background and purpose Our objective was to study the association between the presence of a neurological disease and the comorbidity burden as well as healthcare utilization (HCU). Methods Using baseline data from the Canadian Longitudinal Study on Aging (CLSA), we examined the burden of five neurological conditions. The CLSA is a population‐based study of approximately 50 000 individuals, aged 45–85 years at baseline. We used multivariable Poisson regression to identify correlates of comorbidity burden and HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Further, due to the cross-sectional design, we were unable to tease apart how greater social support may act protectively against physical and mental health factors across the life span. Specifically, aging is associated with an increased risk of multiple comorbid diseases and increased risk of mortality (Wolfson et al, 2019). Thus, if older LGB individuals are disproportionately affected by health inequalities, as other work in the field has demonstrated (Fredriksen-Goldsen et al, 2017;Stinchcombe et al, 2018), it is possible that a survivor effect may be more pronounced among LGB persons.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further, due to the cross-sectional design, we were unable to tease apart how greater social support may act protectively against physical and mental health factors across the life span. Specifically, aging is associated with an increased risk of multiple comorbid diseases and increased risk of mortality (Wolfson et al, 2019). Thus, if older LGB individuals are disproportionately affected by health inequalities, as other work in the field has demonstrated (Fredriksen-Goldsen et al, 2017;Stinchcombe et al, 2018), it is possible that a survivor effect may be more pronounced among LGB persons.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although many national surveys have been published on migraine epidemiology, such as that carried out by Wolfson et al in Canada [1], recent information on the global epidemiological burden of this condition has not been published. Therefore, in this succinct report an update on the worldwide epidemiology of migraine is presented, based on data retrieved from the official database of the World Health Organization (WHO) [2].…”
Section: Dear Editormentioning
confidence: 99%
“…The complex nature of the disease manifests as both motor and non-motor symptoms, and as a result, the affected persons need diverse healthcare services that range from pharmacological management and rehabilitation services to palliative care [3]. Studies have reported that people with Parkinson's disease utilize more healthcare services such as overnight hospitalizations, appointments with physicians and medical specialists, and emergency admissions, beyond the frequency seen in the general Canadian population [4,5]. The literature highlights that access to healthcare services for people with Parkinson's disease is not always easy.…”
Section: Introductionmentioning
confidence: 99%